1978
DOI: 10.1159/000181531
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Studies on Glomeruli in the Congenital Nephrotic Syndrome

Abstract: Morphometric studies were performed on glomeruli in two kidneys of a 13-month-old patient with congenital nephrotic syndrome of the Finnish type (CNF) and two control kidneys from an 11-month-old child. The mean diameter of the glomeruli in the diseased kidneys was abnormally large for the patient’s age and the mean glomerular volume about twice the normal. The number of glomeruli, counted using a statistico-geometrical method, was 74% higher than in the control kidneys, a finding which is in accordance with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Kjessler et al [7] reported a slight increase in glomerular size and number of CNF fetuses of identical gestational age as in this study. The increase in glomerular size in their report was mostly due to the increase in the volume of Bowman's space and not that of the capillary tuft as in Tryggvason s [15] report. The results of the present study are similar to those of Kjessler et al [7].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Kjessler et al [7] reported a slight increase in glomerular size and number of CNF fetuses of identical gestational age as in this study. The increase in glomerular size in their report was mostly due to the increase in the volume of Bowman's space and not that of the capillary tuft as in Tryggvason s [15] report. The results of the present study are similar to those of Kjessler et al [7].…”
Section: Discussionmentioning
confidence: 77%
“…by different techniques [8,14,15], Huttunen et al [6] re ported a lower percentage of immature fetal glomeruli in CNF children under the age of 6 months, but not there after. They suggested that the accelerated maturation of glomeruli possibly begins in the fetal period.…”
Section: Introductionmentioning
confidence: 99%
“…2 Proportion of "normal," microcystic, fetal, and sclerotic glomerular subtypes with advancing ages of patients with congenital nephrotic syndrome of Finnish type (CNF). The mean glomerular volume was significantly higher in CNF than in MCNS patients glomerular size and number in CNF [13,14]. The proportion of "normal" glomeruli was inversely correlated with increasing age, while that of microcystic glomeruli directly correlated with increasing age Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The gene product, nephrin, localizes to the slit pores of the podocytes and has been shown to associate with a ligand, called CD2-associated protein (CD2AP), and to participate in the formation of the filtration barrier [7,8]. The histopathology of the kidney in CNF varies according to the severity and duration of disease, and may show either glomeruli of normal appearance or a combination of fetal, microcystic, and sclerosed glomeruli [1,12,13,14]. Despite these recent advances in understanding the molecular basis of the disease, very little information is available on the structural factors involved in the progression of CNF towards renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation